Translational profiling of clock cells reveals circadianly synchronized protein synthesis. - Huang, Y.; Ainsley, J.A.; Reijmers, L.G.; Jackson, F.R. (PLoS Biology, 2013)
Genome-wide studies of circadian transcription or mRNA translation have been hindered by the presence of heterogeneous cell populations in complex tissues such as the nervous system. We describe here the use of a Drosophila cell-specific translational profiling approach to document the rhythmic "translatome" of neural clock cells for the first time in any organism. Unexpectedly, translation of most clock-regulated transcripts--as assayed by mRNA ribosome association--occurs at one of two predominant circadian phases, midday or mid-night, times of behavioral quiescence; mRNAs encoding similar cellular functions are translated at the same time of day. Our analysis also indicates that fundamental cellular processes--metabolism, energy production, redox state (e.g., the thioredoxin system), cell growth, signaling and others--are rhythmically modulated within clock cells via synchronized protein synthesis. Our approach is validated by the identification of mRNAs known to exhibit circadian changes in abundance and the discovery of hundreds of novel mRNAs that show translational rhythms. This includes Tdc2, encoding a neurotransmitter synthetic enzyme, which we demonstrate is required within clock neurons for normal circadian locomotor activity.